Effect of Different Grasses and Legumes on Aggregate Stability and Infiltration Rates in Red Sandy Clay Loam Soil - Hadimani, A.S.; Gumaste , S.K.; Joshi , V.S.; Patil , S.V. (Journal of Soil and Water Conservation, 2022)
The type of grass and legume and their management influence the soil structure strongly. The main effect is due to the expanding roots which open up the soil and compress it into denser masses along the ’eriphery of their channels. The roots also v the soil from time to time and on drying, .iley leave organic matter distributed through the soil. The fibrous root systems of grasses in particular ramify the soil thoroughly, opening it up, compressing it into lumps, entangling it, drying it and incorporating organic matter in a through fashion. As a